Importance of PPP in water supply sector in developing countries: The case of Georgia - Sulakadze, Rusudan (Journal of Eastern European and Central Asian Research (JEECAR), 2023)
This article presents an empirical study on the effectiveness of Public-Private Partnerships (PPPs) in the water supply industry in Georgia. The study identifies vital and causal problems within the industry, including outdated infrastructure, lack of technical and financial resources in rural areas, absence of consolidated state policy, and insufficient state subsidies. Through a comprehensive assessment that considers economic, social, and environmental sustainability, as well as stakeholder perspectives, the study evaluates the relative importance of different PPP models. Findings indicate that the Build-Operate-Transfer (BOT) model is highly prioritized due to its reliance on private capital and the preservation of state control. The results contribute to evidence-based decision-making, enabling policymakers to design effective PPP frameworks that address the specific needs and characteristics of the water supply industry in Georgia.